RELASI SOSIAL DALAM PRAKTIK KEBIJAKAN CSR - Widhagdha, Miftah Faridl; Wahyuni, Hermin Indah; Sulhan, Muhammad (The Journal of Society and Media, 2019)
This research moved from the limited study of CSR (Corporate Social Responsibility) to beneficiary communities in Indonesia. The theory adapted in this study is the theory of social capital by Woolcock & Narayan. The research method in this study was qualitative with the interpretive descriptive approach of the Neuman model. This study examines forms of social capital in various forms of social relations. The results of this study indicate that there are various forms of social relations that exist in society, namely bonding, bridging and linking.relations Bonding show that intra-group bonds are important to consider in order to maintain group cohesiveness.relations Bridging show that ties between groups need to be built in order to establish cooperation between the target groups and other target groups. Whereasrelations linking indicate that there is a good impact for groups that have a closer relationship with higher power institutions. These results indicate that the three forms of social relations have an impact on the implementation of CSR in a company. This relationship is important to be maintained through communication activities aimed at development carried out through more intensive, open and participatory ways to create healthy and sustainable social relations.